2014
DOI: 10.1262/jrd.2014-023
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Rat and Porcine Retina-derived POU Domain Factor 1 (POU6F2) from a Pituitary cDNA Library

Abstract: Homeobox transcription factors are known to play crucial roles in the anterior lobe of the pituitary gland. During molecular cloning with the Yeast One-Hybrid System using a 5’-upstream region of the porcine Fshβ as a bait sequence, we have cloned a cDNA encoding a partial sequence of the retina-derived POU domain factor 1 (RPF1) from the porcine pituitary cDNA library and confirmed its specific binding to the bait sequence. In situ hybridization was performed to examine localization of Rpf1 and showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The POU family members are transcriptional regulators, many of which are known to control cell type-specific differentiation pathways(22). POU6F2 is involved in the development of the pituitary(23) and kidney(24). Loss of heterozygosity in regions containing POU6F2 has been reported in Wilms tumor(25).…”
Section: Discussionmentioning
confidence: 99%
“…The POU family members are transcriptional regulators, many of which are known to control cell type-specific differentiation pathways(22). POU6F2 is involved in the development of the pituitary(23) and kidney(24). Loss of heterozygosity in regions containing POU6F2 has been reported in Wilms tumor(25).…”
Section: Discussionmentioning
confidence: 99%
“…Reporter assays for the responsive region of Group 3 revealed that these factors regulate Prop1 expression through the most distal region, –2993/–1841 b, possessing two SOX2-binding sites. Notably, we demonstrated that RPF1, which was recently characterized in the pituitary [ 13 ], plays a role in PROP1-positive cells in the early pituitary primordium. On the other hand, PITX2 and SOX11 show unique responses in the –1270/–772 b and –443/–155 b regions, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…Based on the results of the promoter assay, we were interested in RPF1, which was previously demonstrated to be a novel pituitary transcription factor expressed in Rathke’s pouch with a decrease in expression level toward the birth before, and we previously reported that it is a new pituitary transcription factor in the pituitary gland [ 13 ]. Hence, we investigated whether RPF1 and PROP1 coexisted in the early pituitary primordium with in situ hybridization for Rpf1 and immunohistochemistry for PROP1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ARID3A is important for normal embryogenesis, which binds directly to the Oct4, Sox2, Nanog and IgH promoter/enhancer region to activate or repress gene transcription (Webb et al 2011;Popowski et al 2014). PRRX2, also known as S8, is a mesenchymal DNA-binding transcription factor essential for foetal development (Gervais et al 2005), and plays important roles in limb morphogenesis and skeletogenesis (Yoshida et al 2014). Research shows that the highly A-T rich sequence of porcine Fshb promoter region that regulated by PRRX2 and PRRX2 may play a role in suppressing the expression of the Fshb gene (Susa et al 2009).…”
Section: Discussionmentioning
confidence: 99%